Classification and Functional Capabilities of Smart Technologies in the Hotel Industry - Aminova Zarnigor Sodiqovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This article examines the classification and functional capabilities of smart technologies used in the hotel industry. It analyzes major technological categories, including Internet of Things (IoT), artificial intelligence (AI), big data analytics, smart room systems, mobile applications, and digital platforms, and evaluates their role in enhancing service quality, operational efficiency, and customer satisfaction. The study also explores development prospects and challenges of smart technology adoption in hotels within the context of digital transformation.